2005
DOI: 10.1103/physrevc.72.054606
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of QCD factorization at large Feynmanx

Abstract: Recent measurements by the BRAHMS collaboration of high-pT hadron production at forward rapidities at RHIC found the relative production rate (d − Au)/(p − p) to be suppressed, rather than enhanced. Examining other known reactions (forward production of light hadrons, the DrellYan process, heavy flavor production, etc.), one notes that all of these display a similar property, namely, their cross sections in nuclei are suppressed at large xF . Since this is the region where x2 is minimal, it is tempting to inte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
246
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(256 citation statements)
references
References 74 publications
(121 reference statements)
10
246
0
Order By: Relevance
“…Our calculations are fully constrained by existing DIS data [12] and provide an upper limit on nuclear modification from dynamical high-twist shadowing. Deviations between the calculations and the existing data are indicative of inelastic scattering in nuclei [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our calculations are fully constrained by existing DIS data [12] and provide an upper limit on nuclear modification from dynamical high-twist shadowing. Deviations between the calculations and the existing data are indicative of inelastic scattering in nuclei [22].…”
Section: Discussionmentioning
confidence: 99%
“…In a model of Sudakov suppression, Ref. [22], it was shown that the effect is amplified at forward Feynman x, x F → 1.…”
Section: Energy Loss In Cold Nuclear Mattermentioning
confidence: 99%
See 1 more Smart Citation
“…at large Feynman x F ) one faces the energy sharing problem [65]: it is more difficult to give the whole energy to one particle in p − A, than in p − p collision. This effect leads to a breakdown of QCD factorization and to nuclear suppression observed at forward rapidities [65,66,67,68] in any reaction measured so far, even at low energies, where no shadowing is possible.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Single jet production is expected in color glass condensate theories [16], with a parton from the deuteron scattering off the low-x gluon field of the Au nucleus. The away-side suppression may also have explanations via other mechanisms [17].…”
Section: Jets At Forward Anglesmentioning
confidence: 99%